Brain-controlled cinematic interactions - Ramchurn, Richard (2020)
Interactive films have been around for almost a century, yet they have suffered repeatedly from critical, commercial and interactional failings. We propose that brain-computer interfaces can offer interactions with narratives and encourage cinematic engagement by minimising active control. We ask what are the problems inherent to interactive cinema? Can real-time interactions via a brain-computer interface (BCI) construct cinematic content? And how do groups of individuals experience brain-controlled cinema designed for individual, shared or distributed control? Our review of related work motivates the interactional choice of using Passive BCI with real-time cinematic construction to synchronise rhythms of the viewers blinking, Attention and Meditation to the rhythms of cinema. We use the Performance Led Research in-the-Wild methodology to probe public deployments of our films, and we describe user interactions in-the-Wild during screenings of multiple designs of two interactive films: three single user, three multi user, and a live score performance. Our descriptions of BCI mappings to cinematic techniques and production strategies to produce interactive content efficiently contributes to the understanding of practical interactive cinema production. In our results we define 1) different stages of control; discovery, conscious and unconscious, 2) awareness of the affective loop, 3) a shifting prominence of engagement between the narrative, the visual qualities and the agency of users’ interactions. We offer a dynamic view of control; people’s experiences are shifting from awareness of their self, the film, and their control. Our hyper-scanning multi-user study introduces the concept of effects moving across groups, working together to produce engaging experiences, and instances of group members disrupting other’s experience by deciding to unilaterally take control of the film. Our discussion contributes to our understanding of passive interactions with narrative systems. Our research contributions include our insights into seven designs of two brain-controlled films. We define two taxonomies, of control and group control, and produce insights into value to audiences of brain-controlled films. We show the development of affective loops of physiological response and cinematic content, and provide new design directions and practical implications for interactive filmmakers.